Does Nitric Oxide Intake Affect Post-Exercise Recovery in Athletes? A Study on Cocoa, Caffeine and Nitric Oxide Supplement: Effect of Nitric Oxide Intake in Athletes - Mor, Ahmet; Yılmaz, Ali Kerim; Acar, Kürşat; Birinci, Mürşit Ceyhun; Ipekoglu, Gökhan (Progress in Nutrition, 2020)
Background: The beneficial effect of popular supplements and use of nitric oxide (NO) precursor nutrients in athletes which aim at increase of sports performance. Objective: The aim of this study is to investigate the effect of nitric oxide precursor nutrients and some nutrients with the ability to increase NO levels in the body on increased NO production in metabolism and on the recovery after acute exercise. Materials and Methods: 8 volunteers, male athletes, in shape and trained participated into this study. Athletes were subject to research protocol every other day, a total of three times. Heart rate and lactate levels were determined at resting and recovery. Results: Statistically significant difference was detected between control and cocoa/caffeine (CC) groups in the 1 minute lactate levels. Lactate levels significantly decreased in the CC group compared to the control group in the 1 minute lactate levels (p<0.05). Statistical significance difference was found between the nitric oxide supplement (NOX) and CC groups in the 1 and 10 minutes heart rate levels. Heart rate levels significantly decreased in the CC group compared to the NOX group (p<0.05). Heart rate levels were significantly decreased in the CC group compared to the control and NOX groups in the 15 minute measurement (p<0.05). Conclusions: Nitric oxide consumed as a supplement in line with nutrition and recovery strategies in athletes improved the recovery by accelerating lactate excretion from the body after the exercise. All of these metabolic responses in the present study suggest that NO will have a positive effect on exercise performance and recovery.